Tourism and souvenirs glocal perspectives from the margins - Cave, Jenny; Jolliffe, Lee; Baum, Tom (Channel View Publications, 2013)
This book situates souvenirs as tangible and intangible expressions and triggers of tourism experience that are 'glocally' developed on the margins. The authors gain new insights with this critique of souvenirs that situates souvenirs of place, people and experience as constructions of transnational lives, migration and global tourism.